Specification for metal-clad base materials for printed circuits. Thin epoxide woven glass fabric copper-clad laminated sheet of defined flammability for use in the fabrication of multilayer printed boards: EP-GC-Cu-12 Part 12, (30th September 1982) - British Standards Institution,
No abstract available